2012
DOI: 10.1182/blood-2011-07-369595
|View full text |Cite
|
Sign up to set email alerts
|

Increased BMI correlates with higher risk of disease relapse and differentiation syndrome in patients with acute promyelocytic leukemia treated with the AIDA protocols

Abstract: We investigated whether body mass index (BMI) correlates with distinct outcomes in newly diagnosed acute promyelocytic leukemia (APL). The study population included 144 patients with newly diagnosed and genetically confirmed APL consecutively treated at a single institution. All patients received All-trans retinoic acid and idarubicin according to the GIMEMA protocols AIDA-0493 and AIDA-2000. Outcome estimates according to the BMI were carried out together with multivariable analysis for the risk of relapse an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 31 publications
4
33
1
Order By: Relevance
“…19 The results of a recently published study of children and adults with APL showed that overweight/obese patients had a significantly higher relapse rate and incidence of differentiation syndrome. 20 These results may suggest a relationship between obesity-related metabolic mediators and the pathogenesis of APL.…”
Section: Discussionmentioning
confidence: 85%
“…19 The results of a recently published study of children and adults with APL showed that overweight/obese patients had a significantly higher relapse rate and incidence of differentiation syndrome. 20 These results may suggest a relationship between obesity-related metabolic mediators and the pathogenesis of APL.…”
Section: Discussionmentioning
confidence: 85%
“…The adverse impact of obesity beginning at time of diagnosis on EFS and disease-related mortality has been demonstrated across multiple studies in pediatric ALL, [2][3][4][5]28 adult ALL, 39 and other hematologic malignancies. [40][41][42] The newly identified effect of obesity to increase risk for persistent MRD raises the question of whether obese patients should be considered as a higher risk group from time of diagnosis, analogous to adolescents, who could potentially benefit from more intensive therapy during induction. Alternatively, and in contrast to immutable host and leukemia risk factors, the added risk from obesity may be modifiable and amenable to intervention as suggested in CCG1961 in which normalization of BMI mitigated the adverse impact on EFS.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the impact of the PML/RARA transcript, several studies [3,6,13,14] have previously reported a trend toward an inferior outcome for BCR3 isoform. On a more mature follow-up, we previously found [15] that patients with BCR3 transcript had a significantly higher relapse rate. A long-term follow-up analysis of our patient series also revealed that FLT3-ITD confers poor prognosis, with a 9 years OS of 96% in the FLT3-ITD2ve cohort compared to 39% in the FLT3-ITD1ve cohort and 9-year CIR rates of 4% and 60% for the FLT32ve and FLT31ve cohorts, respectively [12].…”
mentioning
confidence: 89%